Model Bahan Ajar Menulis Teks Deskripsi Berbasis Kearifan Lokal Banten dengan Media Powtoon dan Flipped Classroom - Litteu Nur El Lailatie; Endry Boeriswati; Samsi Setiadi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to determine the effectiveness of audiovisual learning media in the form of learning videos in improving the understanding and writing skills of descriptive texts of grade VII students through the integration of Banten local wisdom. The product developed is a Powtoon-based learning video containing essential concepts regarding descriptive texts. The media implementation is carried out through the flipped class model, namely by distributing learning videos through the WhatsApp application so that students can study the material independently before attending class. This study uses the Research and Development (R&D) method that focuses on the process of designing, developing, testing, and refining learning products. The results show that audiovisual learning media is able to accommodate various learning styles of students, increase their involvement in the learning process through the presentation of interesting, easily accessible, and contextual materials, and support a more optimal understanding of concepts. In addition, the application of the flipped class model encourages students' learning independence because they have obtained initial knowledge before face-to-face learning activities take place. Thus, the development of this learning media has the potential to improve the quality and effectiveness of learning to write descriptive texts at the junior high school level.